2001
DOI: 10.1016/s0022-5347(05)65982-4
|View full text |Cite
|
Sign up to set email alerts
|

Detrusor Instability in Men: Correlation of Lower Urinary Tract Symptoms With Urodynamic Findings

Abstract: Detrusor instability and bladder outlet obstruction are common in men with lower urinary tract symptoms. The symptom of urge incontinence strongly correlated with detrusor instability. Other lower urinary tract symptoms did not correlate well with any urodynamic findings. Therefore, we believe that an accurate urodynamic diagnosis may enable focused and more efficient management of lower urinary tract symptoms in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 15 publications
0
91
0
7
Order By: Relevance
“…A possible reason for the difference in the uNGF levels between OAB-dry and OAB-wet could be the different degrees of inflammation and a higher percentage of DO (detrusor overactivity) in patients with OAB-wet. Hyman et al (2001) found a higher incidence of DO associated with urgency incontinence (OAB-wet) than with the symptoms of urgency and frequency or nocturia or difficult urination (75 vs 36%). Hashim and Abrams (2006) also found that 69% of men and 44% of women with OAB-dry had DO, while 90% of men and 58% of women with OAB-wet had DO.…”
Section: Discussionmentioning
confidence: 95%
“…A possible reason for the difference in the uNGF levels between OAB-dry and OAB-wet could be the different degrees of inflammation and a higher percentage of DO (detrusor overactivity) in patients with OAB-wet. Hyman et al (2001) found a higher incidence of DO associated with urgency incontinence (OAB-wet) than with the symptoms of urgency and frequency or nocturia or difficult urination (75 vs 36%). Hashim and Abrams (2006) also found that 69% of men and 44% of women with OAB-dry had DO, while 90% of men and 58% of women with OAB-wet had DO.…”
Section: Discussionmentioning
confidence: 95%
“…When considering our results in a wider clinical context, it is interesting to note that the type of LUTS experienced by men does not always correlate with actual pathophysiological changes. For example, Hyman et al 26 showed that detrusor instability, measured in 160 men, only correlated with urge incontinence (and no other IPSS storage symptoms). In addition, 68% of the men they evaluated had measurable BOO, regardless of the main complaint.…”
Section: Discussionmentioning
confidence: 99%
“…Knutson et al showed DO accompany 55% of patients with LUTS by urodynamic studies (9). Hyman et al stated 46% of patients having LUTS also suffer from DO in 109 patients with LUTS or bladder outlet obstruction (BOO) (10). Similar studies showed this combination can be seen up to 75% of cases (2,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 95%